1986
DOI: 10.1042/bj2400471
|View full text |Cite
|
Sign up to set email alerts
|

Studies on myelin-basic-protein methylation during mouse brain development

Abstract: The synthesis and methylation in vivo of myelin basic protein (MBP) during the mouse brain development has been investigated. When mice ranging in age from 13 to 60 days were injected intracerebrally with L-[methyl-3H]methionine, the incorporation of radioactivity into MBP isolated from youngest brain was found to be the highest and declined progressively in mature brains. This pattern of radioactivity incorporation was inversely correlated with the total amount of MBP in the brains, suggesting a higher ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 41 publications
(47 reference statements)
1
16
0
Order By: Relevance
“…Thus, although we consider that PTMs modulate MBP's conformation, even highly-modified MBP is still an IUP that, on its own, would not attain a defined fold driven by formation of a hydrophobic core. Brostoff and Eylar (1971), Baldwin and Carnegie (1971a,b), Chanderkar et al (1986), Kim et al (1988Kim et al ( , 2003 and Pritzker et al (2000b) 108-GLSLS-112 113 Arg R Potentially deiminated Wood et al (1996) 114 Phe F 115 Ser S Phosphorylated Turner et al (1984), Kishimoto et al (1985) and Kim et al (2003) 116-WGAEG-120 121 Gln Q Deamidated Kim et al (2003) 122 Arg R Deiminated Wood and Moscarello (1989) and Kim et al (2003) 123-PGFGYGG-129 130 Arg R Deiminated Wood and Moscarello (1989) and Kim et al (2003) 131-ASDYK-135 136 Ser S Phosphorylated Kishimoto et al (1985) 137-AHKGFKGVDA-146 147 Gln Q Deamidated Chou et al (1976), Zand et al (1998) and Kim et al (2003) 148 Gly G 149 Thr T Phosphorylated Kim et al (2003) 150 Leu L 151 Ser S Phosphorylated Kishimoto et al (1985) and Kim et al (2003) 152-KIFKLGG-158 159 Arg R Deiminated; methylated Wood and Moscarello (1989) and Kim et al (2003) 160 Asp D 161 Ser S Phosphorylated Kishimoto et al (1985) and Zand et al (1998) Kishimoto et al (1985), Zand et al (1998) and Kim et al (2003) 166-PMA-168 169 Arg R Potentially deiminated Wood et al (1996) 170 Arg R Deiminated Wood and Moscarello (1989) Data have been adapted from and Wood and Moscarello (1997), with addition of more recent data from Kim et al (2003). In extreme cases of fulminating MS, arginyl residues at potentially all sites can be deiminated (W...…”
Section: Modifications To the 185 Kda Mbp Isoformmentioning
confidence: 96%
“…Thus, although we consider that PTMs modulate MBP's conformation, even highly-modified MBP is still an IUP that, on its own, would not attain a defined fold driven by formation of a hydrophobic core. Brostoff and Eylar (1971), Baldwin and Carnegie (1971a,b), Chanderkar et al (1986), Kim et al (1988Kim et al ( , 2003 and Pritzker et al (2000b) 108-GLSLS-112 113 Arg R Potentially deiminated Wood et al (1996) 114 Phe F 115 Ser S Phosphorylated Turner et al (1984), Kishimoto et al (1985) and Kim et al (2003) 116-WGAEG-120 121 Gln Q Deamidated Kim et al (2003) 122 Arg R Deiminated Wood and Moscarello (1989) and Kim et al (2003) 123-PGFGYGG-129 130 Arg R Deiminated Wood and Moscarello (1989) and Kim et al (2003) 131-ASDYK-135 136 Ser S Phosphorylated Kishimoto et al (1985) 137-AHKGFKGVDA-146 147 Gln Q Deamidated Chou et al (1976), Zand et al (1998) and Kim et al (2003) 148 Gly G 149 Thr T Phosphorylated Kim et al (2003) 150 Leu L 151 Ser S Phosphorylated Kishimoto et al (1985) and Kim et al (2003) 152-KIFKLGG-158 159 Arg R Deiminated; methylated Wood and Moscarello (1989) and Kim et al (2003) 160 Asp D 161 Ser S Phosphorylated Kishimoto et al (1985) and Zand et al (1998) Kishimoto et al (1985), Zand et al (1998) and Kim et al (2003) 166-PMA-168 169 Arg R Potentially deiminated Wood et al (1996) 170 Arg R Deiminated Wood and Moscarello (1989) Data have been adapted from and Wood and Moscarello (1997), with addition of more recent data from Kim et al (2003). In extreme cases of fulminating MS, arginyl residues at potentially all sites can be deiminated (W...…”
Section: Modifications To the 185 Kda Mbp Isoformmentioning
confidence: 96%
“…Likewise, both yeast Npl3p (10) and mammalian hnRNPs (23) reside predominantly in VOL. 16,1996 hnRNP METHYLTRANSFERASE IN S. CEREVISIAE 3675 on May 12, 2018 by guest http://mcb.asm.org/ nuclei. A nuclear localization would mean that these proteins are methylated after they are imported into nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…(Rat hnRNP A1 protein, expressed and isolated from E. coli, was previously shown to contain no methylated arginine residue, indicating VOL. 16,1996 hnRNP METHYLTRANSFERASE IN S. CEREVISIAE 3673 on May 12, 2018 by guest http://mcb.asm.org/ that E. coli does not modify these residues [16].) The proteins were resolved by SDS-PAGE, and labeling was detected by fluorography.…”
Section: Hmt1p Immunopurified From Yeast Cells Methylates Npl3p In VImentioning
confidence: 99%
“…Isolation and analysis of MBP revealed that it contains a methylated Arg residue [position 107] that is present both in mono-and di-methylated forms (102) (mono, 0.4-0.8 mol/mol MBP; and di, 0.2 mol/mol MBP). Investigations into this feature of MBP (123) have suggested that methylation may represent an important step in the formation of myelin as seen primarily by the observation that, in cultured oligodendroglial cells, inhibitors to the methyl-transferase enzymes produce a significantly less compact myelin (124).…”
Section: Methylationmentioning
confidence: 99%
“…Developmental studies using radioactive tracers have shown that methylation of MBP occurs during the formative stages of myelination and, as with phosphorylation, this modification may constitute an initiation signal (123). The consequences of methylation may manifest themselves through an increase in the hydrophobicity of this region of MBP and, accordingly, increase protein-protein or protein-lipid interactions that may be necessary for MBP function.…”
Section: Methylationmentioning
confidence: 99%